ETIKA PROFETIS CERITA RAKYAT SURAKARTA - U'um Qomariyah; Mukh Doyin; Zuliyanti Zuliyanti; Dyah Prabaningrum (Universitas Negeri Makassar, 2019)
Prophetical Ethics on Folklores of Surakarta. This study aims to describe the humanism, liberation, and transcendence ethics as pillars of prophetical ethics on the folklores of Surakarta. The method of investigation used was descriptive qualitative approach by implementing critical analysis methods with the objects of the study were the folklores spread in regional of Surakarta. The collecting data methods used were a literature review, observation, and interviews and there were analyzed with several steps (1) data reduction, (2) data presentation, and (3) drawing conclusions. The result of the study was, the folklores in Surakarta regions provide prophetical values, namely (1) humanism ethics, including: big soul, caring, apologizer, helper; (2) liberation ethics, including: learning, rights fighters, glory, unity, and (3) ethics of transcendence, including: meditation, surrendered, sincerely, and obedience to leaders.